Repair of Cerebrospinal Fluid Leak After Functional Endoscopy Sinus Surgery - Mohamad I Sapta; Teresa L Wargasetia (Universitas Kristen Maranatha, 2017)
Cerebrospinal fluid (CSF) leak is one of Functional Endoscopic Sinus Surgery (FESS)complications. Since 2001, it was reported that there is one case of CSF leak as FESScomplication in ENT-HN Department, Faculty of Medicine, Maranatha Christian University -Immanuel Hospital in Bandung. The purpose of this case report is present clinical findings andmanagement of CSF leak as FESS complication. A-45 year old male with headache as chiefcomplain after undergone FESS five days before. There was a clear rhinorrhea running frompatient’s right nose. In nasoendoscopic examination, it was showed there was a defect in laminacribrosa. The result of paranasal sinus computed tomography scanning showed an air columnin brain ventricular system. The defect in lamina cribrosa was repaired by transnasalendoscopic using materials such as surgicel, cartilages, and fat tissues. The conclusion is weroll out one case about repair of CSF leak as a FESS complication and it was done with a goodresult.Keywords: cerebrospinal fluid leak, functional endoscopic sinus surgery